“The Body Does Matter”: Women as Embodied Social Subjects in Angela Carter’s ’Nights at the Circus’ - Milosavljević, Tatjana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Postmodernism posed a crucial ontological challenge to reality, questioning what constitutes the real world, simultaneously interrogating the horizon of representation of this unstable reality in fiction. Feminism on the other hand equipped us with critical tools for interpreting the reality of being in the world in a gendered body, as well as with a conceptual apparatus for interpreting the manifold institutional and private oppressions of women’s bodies that play out in women’s daily lives and in the discourses that shape them, literary discourse being one of them. This paper argues that Angela Carter’s 1984 novel Nights at the Circus, which is widely held as a postfeminist text due to its narrative commitment to transcending gender binaries, essentially uses the strategies of postmodern storytelling and characterization in order to explore women’s embodied potentialities of agency i.e. their construction of subjectivity through body. We will argue that the hybrid magic realist narrative constructs Fevvers’ body as a titillating postmodern performance, ontologically illusive and elusive, yet it grounds that same body in various socially effected predicaments and experiences that serve to show that even in the midst of a play of signifiers, in Patricia Waugh’s words, “the body does matter, at least to what has been the dominant perspective within British female fiction” (Waugh, 2006, p. 196). In other words, it may be argued that Carter’s novel is invested in traditional second-wave feminist politics to the extent that it shows that a woman’s body is an indispensible medium of being in the world with material consequences that bear on the formation of her subjectivity and possibility of agency, and through which she acts out her relationships to others and is acted upon.